2008
DOI: 10.1021/jp801276p
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Photoinduced Charge Separation in Naphthalene Diimide Based Multichromophoric Systems in Liquid Solutions and in a Lipid Membrane

Abstract: The photophysical properties of multichromophoric systems consisting of eight red or blue naphthalene diimides (NDIs) covalently attached to a p-octiphenyl scaffold, as well as a blue bichromophoric system with a biphenyl scaffold, have been investigated in detail using femtosecond time-resolved spectroscopy. The blue octachromophoric systems have been recently shown to self-assemble as supramolecular tetramers in lipid bilayer membranes and to enable generation of a transmembrane proton gradient upon photoexc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
95
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 77 publications
(151 reference statements)
11
95
1
Order By: Relevance
“…The spectrum above 450 nm is very similar to that of R1 •-generated upon photoinduced CS between R1 in the lowest singlet excited state and an electron donor. 41 On the other hand, the negative TA band below 450 nm coincides very well with the S 0 f OPE-LES absorption band and can be assigned to the bleach of this transition. These TA spectra present very small changes with time, except for the intensity that decays almost entirely to zero after about 1.5 ns.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…The spectrum above 450 nm is very similar to that of R1 •-generated upon photoinduced CS between R1 in the lowest singlet excited state and an electron donor. 41 On the other hand, the negative TA band below 450 nm coincides very well with the S 0 f OPE-LES absorption band and can be assigned to the bleach of this transition. These TA spectra present very small changes with time, except for the intensity that decays almost entirely to zero after about 1.5 ns.…”
Section: Resultsmentioning
confidence: 56%
“…This positive amplitude is also probably associated with the NDI-LES, which has previously been shown to absorb between 400 and 500 nm. 41 The spectra associated with the longest time constants, τ 3 and τ 4 , are very similar and are essentially equal to the TA spectrum of the OPE/NDI-CSS. Therefore, these two time constants can be attributed to the decay of the OPE/NDI-CSS population back to the ground state upon CR (pathway 9 in Figure 5).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…[17][18][19][20][21] The deactivation via hydrogen-bond-assisted proton transfer has been reported for methyl salicylate, 22 anthraquinones, 23,24 and some other aromatic molecules. [25][26][27][28][29][30] A fast deactivation of the photoexcited state was also found with o-aminoacetophenone (AAP) and its derivatives, whose chemical structures are similar to that of KN. 31,32 It has been shown that internal conversion (IC) is the main decay channel of the S 1 state, and that its rate constant is highly sensitive to the solvent: in polar aprotic solvents, the fluorescence lifetime of AAP exceeds 1 ns, while in polar protic and nonpolar solvents it decreases by one and two orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%